Searching a spring wheat mutation resource for correlations between yield, grain size, and quality parameters. Issue 2 (4th March 2017) - Kenzhebayeva, Saule S.; Doktyrbay, Gulina; Capstaff, Nicola M.; Sarsu, Fatma; Omirbekova, Nargul Zh.; Eilam, Tamar; Tashenev, Dauren K.; Miller, Anthony J.
ABSTRACT: To broaden genetic variation, an irradiated wheat ( Triticum aestivum L.) M5 population was generated in the background of spring wheat cv. Almaken. This resource was used to measure components of productivity, including grain number and grain weight (GW) per main spike, GW per plant (GWP), 1000-grain weight (TGW), grain size and grain shape, and some quality parameters. Some mutant lines, mostly in the 200-Gy-dosed germplasm, had 2–4 times higher grain iron and zinc concentrations and 7–11% higher protein content relative to the parent line. Some irradiated lines had significantly larger TGW, and grain area (GA), length, and width than the parent, cv. Almaken. The largest GA and grain length (GL) were 30–40% greater than those of the parent. Correlations for Zn concentration versus GA = 0.191, p ˂ 0.01, grain protein content (GPC) versus GA = 0.128, p ˂ 0.05, GPC versus GL = 0.113, p ˂ 0.05, and GPC versus grain width = 0.191, p˂0.001 were observed in 200 Gy-dosed mutants. In 100 Gy-dosed mutants, correlations for Fe concentration versus GWP = 0.302, p ˂ 0.001 and Fe concentration versus TGW = 0.153, p ˂ 0.01 were found. The mutant lines showed the capacity to biofortify wheat grain without negatively impacting on crop productivity and this population offers promising donors for improving grain parameters such as GA, length, and width and quality. The data presented showed how the genetic variation generated through radiation could be used to test the linkage between various important grain parameters.